2018
DOI: 10.1001/jamacardio.2018.0653
|View full text |Cite
|
Sign up to set email alerts
|

Association of Fibroblast Growth Factor 23 With Recurrent Cardiovascular Events in Patients After an Acute Coronary Syndrome

Abstract: In patients stabilized after ACS, elevated FGF-23 concentrations may be associated with recurrent major CV events and all-cause mortality, providing information independent of established clinical risk factors and cardiorenal biomarkers. A potential sex difference in these findings deserves further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 46 publications
2
28
1
1
Order By: Relevance
“…When renal function declines in patients with chronic kidney disease the concentration of circulating FGF-23 is increased in response to persistent hyperphosphatemia [ 4 ]; however, increased levels of FGF-23 have also been associated with an increased risk of developing heart failure, cardiovascular disease, and cardiovascular death independent of renal function and other cardiovascular risk factors [ 5 , 6 ]. In patients with combined type 2 diabetes and CAD, FGF-23 independently predicts adverse cardiovascular outcome [ 7 ] and, additionally, elevated FGF-23 concentrations following acute coronary syndrome are associated with an increased risk of CV death and hospitalization due to heart failure [ 8 ]. Furthermore, a recent study of patients with type 2 diabetes and normal or mildly impaired kidney function showed that FGF-23 was associated with an increased risk of both major adverse cardiovascular events and all-cause mortality [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…When renal function declines in patients with chronic kidney disease the concentration of circulating FGF-23 is increased in response to persistent hyperphosphatemia [ 4 ]; however, increased levels of FGF-23 have also been associated with an increased risk of developing heart failure, cardiovascular disease, and cardiovascular death independent of renal function and other cardiovascular risk factors [ 5 , 6 ]. In patients with combined type 2 diabetes and CAD, FGF-23 independently predicts adverse cardiovascular outcome [ 7 ] and, additionally, elevated FGF-23 concentrations following acute coronary syndrome are associated with an increased risk of CV death and hospitalization due to heart failure [ 8 ]. Furthermore, a recent study of patients with type 2 diabetes and normal or mildly impaired kidney function showed that FGF-23 was associated with an increased risk of both major adverse cardiovascular events and all-cause mortality [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a higher occurrence of recurrent cardiovascular events in the highest quartile of FGF-23 in patients with acute coronary syndrome as well as worse outcomes in patients with known RD, including increased frequency of heart failure and mortality 11,12,28 . A population-based study of stroke-free individuals found that FGF-23 is a risk factor for subsequent stroke independent of RD 29 , an association in CSVD with progressing vascular disease has not yet been reported.…”
Section: Discussionmentioning
confidence: 91%
“…With a series of eligible compounds available at present, scientists would be admired if they exerted more effort in exploring the role of Lp‐PLA2 in diseases other than atherosclerosis, particularly, in microvascular diseases that may be more sensitive to Lp‐PLA2 inhibition. In addition, the large pool of data generated from clinical trials provides numerous opportunities for comprehensive data mining, which may be beneficial to understanding the biological consequences of Lp‐PLA2 inhibition and help us to learn a profound and valuable lesson from the failure of darapladib . To conclude, we anticipate that the story of Lp‐PLA2 will continue.…”
Section: Discussion and Prospectsmentioning
confidence: 99%
“…In addition, the large pool of data generated from clinical trials provides numerous opportunities for comprehensive data mining, which may be beneficial to understanding the biological consequences of Lp-PLA2 inhibition and help us to learn a profound and valuable lesson from the failure of darapladib. [279][280][281][282][283][284][285][286][287][288] To conclude, we anticipate that the story of Lp-PLA2 will continue.…”
mentioning
confidence: 98%